Sister Society Meeting on Global Education Development and Collaboration: Meeting Report. Issue 6 (1st July 2016) - Chuang, Linus T.; Randall, Thomas C.; Denny, Lynette; Johnston, Carolyn M.; Schmeler, Kathleen M.; Covens, Allan L.; Cibula, David; Bookman, Michael A.; Rawal, Sudhir; DePetrillo, Denny; Nam, Joo-Hyun; Goodman, Annekathryn; et al.
Abstract : Objectives: To identify common barriers to teaching and training and to identify strategies that would be useful in developing future training programs in gynecologic oncology in low- and middle- income countries. Methods: There is a lack of overall strategy to meet the needs of education and training in gynecologic oncology in low- and middle- income countries, the leaderships of sister societies and global health volunteers met at the European Society of Gynecologic Oncology in October 23, 2015. The challenges of the training programs supported by gynecologic oncology societies, major universities and individual efforts were presented and discussed. Strategies to improve education and training were identified. Results: Major challenges include language barriers, limited surgical equipment, inadequate internet access, lack of local support for sustainability in training programs, inadequate pathology and radiation oncology, finance and a global deficiency in identifying sites and personnel in partnering or developing training programs. The leaderships identified various key components including consultation with the local Ministry of Health, local educational institutions; inclusion of the program into existing local programs, a needs assessment, and the development of curriculum and regional centers of excellence. Conclusions: Proper preparation of training sites and trainers, the development of global curriculum, the establishment of centers of excellence, and the ability to measure outcomes are important to improve education and training in gynecologic oncology in low- and middle- income countries.